Constructing ’the people’ Citizen populism against ethnic hegemony in Bosnia–Herzegovina in the light of the 2013– 2014 protests - Stipic, Igor (Socio.hu Társadalomtudományi Szemle, 2017)
This article, essentially following the contributions of Gramsci and Laclau on hegemony and populism (a non–normative view), analyzes the possibilities for Bosnian–Herzegovinian (BiH) society to challenge its predominantly unaccountable and authoritarian political structures, taking as a point of departure the 2013– 2014 outburst of protests and social mobilization. The analysis is situated in a context of specific cultural and social conditions marked by the ideological hegemony of ethnic discourse. In this sense, unprecedented levels of solidarity among BiH ethnic societies by signaling an end to chronic depolitization that had plagued this socio–political space ever since the transition to democracy, served as an opportunity for the construction of a new universal signification that could break with the coherence of the existing discourse and offer an antagonistic frontier different than the one characterized by the ethnic question. This incipient appearance of a social project rivaling deeply entrenched ethnic democracy, appearing in the times of (minor) organic crisis, offered, mainly through the logic of displacement of an already established political frontier, a new perspective on the BiH political scene. This war of position, in our view, provides fertile ground for the development of what could be defined as citizen populism. As such, by taking the BiH citizens, the system outcasts par excellence, to the center of the political stage, social movements offer a chance to replace the well–established notion of ethnic subjects with that of fully–fledged citizens. Additionally, this article considers the problematique of building bonds of equivalences in both socially and ethnically heterogeneous social movements that demand accountability from existing structures, while rejecting its own projection via political society, a sin qua non for representation of demands. Keywords: Bosnia–Herzegovina, hegemony, populism, social movements.